A classification of flag‐transitive point‐imprimitive 2‐designs with block size 6. Issue 4 (12th October 2017) - Zhan, Xiaoqin; Zhou, Shenglin
Abstract: We determine all 2‐ ( v, 6, λ ) designs admitting a flag‐transitive point‐imprimitive automorphism group.